"More than blowing bubbles": What parents want from therapists working with children with autism spectrum disorder. (2nd September 2016) - Edwards, Amelia; Brebner, Chris; Mccormack, Paul F.; Macdougall, Colin
Abstract: Purpose : Providing therapy to children with autism spectrum disorder (ASD) often requires therapists to work closely with both the child with ASD and their family. Although there is evidence outlining best practice for therapists when working with families of children with disabilities, few studies have examined the parental perspective. This study investigated the qualities parents seek in therapists who work with their children with ASD. Method : Semi-structured interviews were conducted with 14 parents of children with ASD. Thematic analysis was undertaken to analyse the data, with emergence of two core themes; Partnership and Effective Therapy. Result : The parents of children with ASD interviewed for this study valued both working in partnership with therapists and therapists delivering effective therapy. Parents ultimately wanted therapists to produce positive outcomes for their children and were willing to sacrifice other desired qualities, as long as the therapy program was effective. Conclusion : While parents of children with ASD identified a range of qualities that they want in therapists, a therapist being able to produce positive outcomes for their child was considered most important. The implications of these findings are discussed both in terms of clinical implications for therapists and directions for future research.